ICEBERG: An Internet-core Network Architecture for Integrated Communications - Wang, Helen; Raman, Bhaskaran; Chuah, Chen-nee; Biswas, Rahul; Gummadi, Ramakrishna; Hohlt, Barbara; Hong, Xia; Kiciman, Emre; Mao, Zhuoqing; Shih, Jimmy S.; Subramanian, Lakshminarayanan; Zhao, Ben Y.; et al. (IEEE Personal Communications: Special Issue on IP-based Mobile Telecommunications Networks, 2000)
In the ICEBERG project at U.C. Berkeley, we are developing an Internet-based integration of telephony and data services spanning diverse access networks. Our primary goals are extensibility, scalability, robustness and personalized communication. We leverage the Internet's low cost of entry for service creation, provision, deployment, and integration. In this article, we present our solutions to signaling, easy service creation, resource reservation, admission control, billing and security in the ICEBERG network architecture.